Deteksi dini skoliosis di tingkat Sekolah Dasar Katolik Santo Yoseph 2 - Cok Gde Prema Kurnia Baswara; I Wayan Weta; Luh Seri Ani (Intisari Sains Medis, 2019)
Introduction: The number of cases of scoliosis found in the world is high reach 4.5% of the total world general population, while for Indonesia and Bali there has been no incidence rate for the scoliosis. The most common case of scoliosis found is idiopathic as much as 80% of the total cases found so far. Early detection of this scoliosis plays a role to know early on whether there are abnormalities in the spine or not and if there is can to be prevented from getting worse.Method: This study is an observational descriptive study by directly measuring the spine of elementary school students by using a scoliometer.Result: Total of 96 primary school students who met the inclusion and exclusion criteria, the most sexes were women with 51 students (53.1%), who were suspected of having scoliosis were 62 (64.4%), on adolecent suspected of scoliosis with 39 students (81,3%) and scoliosis criteria was mostly found in intermediate criteria of 55 students (88,7%)Conclusion: The prevalence of scoliosis in primary school students is 88%, most scoliosis criteria are found at the intermediate level, and female sex is more likely to have scoliosis than men